Targeting osteosarcoma vasculature with peptide obtained by phage display - Guan, Mingqiang; Wang, Jian; Yang, Lanbo; Zhao, Zandong; Lu, Kun; Zhao, Liang; Xiao, Jun; Li, Zhihan; Shi, Zhanjun (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: Tumour endothelial cells have been proven to have molecular markers distinct from normal endothelial cells. These specific molecular markers allow for targeting of the tumour vasculature with specific pharmacological vehicles to direct diagnostic or therapeutic modalities at the endothelial cells. By performing a phage display-based screening, this study aimed to identify a certain short peptide that could specifically bind to osteosarcoma vasculature. Material and methods : We performed in vivo screening in the murine models of osteosarcoma with annular Ph.D.-C7C library in the present study. To explore the in vivo binding specificity of the retrieved peptide, we conjugated the peptide with fluorescein isothiocyanate (FITC) and injected it intravenously into osteosarcoma-bearing BALB-c mice. Results: CTKPDKGYC was the dominant sequence isolated from in vivo screening and was named as NF-1. Fluorescence staining found that FITC-NF-1 peptide could be specifically homed to osteosarcoma vasculature while being almost undetectable in the heart, brain, lung and liver. Simultaneously, a small amount of fluorescence could also be detected in the renal glomerulus and renal tubule but not in renal vascular endothelium, indicating that FITC-NF-1 peptide might be excreted mainly through the renal-urinary route. Conclusions: Our data suggest that, with high binding specificity to osteosarcoma vasculature, peptide NF-1 may have potential value in early diagnosis or targeted therapy for osteosarcoma.